Genetic Variability and Association Analysis in Madhuca indica GMEL - Wani, Mohd. Saleem; Wani, Afaq Majid (Indian Forester, 2013)
Twenty genotypes of Madhuca inidica Gmel. scattered over district Allahabad, and adjoining areas in Uttar Pradesh in their natural range were studied for the pattern of genetic variation. Higher values for phenotypic coefficient of variation as compared to genotypic coefficient of variation in germination and nursery growth parameters, indicate that they are greatly influenced by the environment. The heritability and expected genetic gain were also observed to be high for these characters, except for number of leaves per seeding, leaf area, shoot/root ratio and total biomass of seedling. The correlations between germination per cent, germination energy index per cent,mean daily germination, seedling height, seedling collar diameter and internodal length at phenotypic level were positive and significant. The families F15, F18, F19 and F20 showed good performance and are recommended for further genetic improvement programme in this species.